PENGARUH HARGA, LOKASI, DAN KUALITAS PELAYANAN JASA TERHADAP KEPUASAN KLIEN DI NOTARIS DAN PPAT WITRIE NUR AIDA, S.H.,M.Kn KABUPATEN KEDIRI - Dewi, Rheka Rahmawati Sari; Rusandy, Deby Santyo; Widuri, Trisnia (Commodities, Journal of Economic and Business, 2022)
One of the growing businesses is the legal services sector, specifically in the field of notary and land deed-making services (PPAT - Pejabat Pembuat Akta Tanah). The office of Notary and PPAT Witrie Nur Aida, SH, MKn. operates in the legal services field using pricing, location, and service quality strategies to achieve the goal of client satisfaction. The location of the Notary and PPAT office of Witrie Nur Aida, SH, MKn. is strategic, as it is situated on the border between Kediri City and Kediri Regency. However, the notary office's location does not have ample parking facilities, causing clients difficulties in parking their vehicles. The quality of service provided by the Notary Witrie Nur Aida, SH, MKn. office includes timely handling of client documents and a friendly staff. This study is a quantitative research. The research is conducted at the Notary and PPAT Witrie Nur Aida, SH, MKn. office. The population of this study consists of 153 individuals. The sample size is 111, determined using the Slovin formula as the sampling technique. The analysis techniques used include validity and reliability tests, classic assumption tests, and hypothesis testing. Partially, the Price variable (X1) has a significant influence on the client satisfaction variable (Y). Partially, the Location variable (X2) has a significant influence on client satisfaction (Y). Partially, the Service Quality variable (X3) has a significant influence on client satisfaction (Y). Simultaneously, price, location, and service quality have a significant impact on client satisfaction.